Perbedaan karakter vegetatif beberapa galur harapan jagung AMP-UNIPA di Kampung Webi, Distrik Rasiei, Kabupaten Teluk Wondama - Ika Yulianti, Tyfenberlis; Mawikere, Nouke Lenda; Abbas, Barahima; Wibawati, Zarima; Dare, Darius (Cassowary, 2026)
Corn (Zea mays L.) is a strategic food commodity that supports food diversification, particularly in eastern Indonesia. The development of red corn is significant due to its potential as a functional food. However, local corn productivity is generally low, requiring improvement through breeding. This study aims to compare the vegetative characteristics of several genotypes of the AMP-UNIPA promising line cultivated in Webi Village, Rasiei District, Teluk Wondama Regency. The study was designed using a Randomized Block Design (RBD) with 13 corn genotypes, consisting of AMP-UNIPA 1–9 and 4 comparison genotypes (Local Red Anggi, Waxy-corn, Local Wondama, and National Variety). The parameters observed included plant height, number of leaves, leaf length, leaf width, leaf color, stem diameter, length of the 3rd stem node, length of the 4th stem node, number of stem nodes, and stem color. Data were analyzed using ANOVA and HSD at a 95% confidence level. The results showed significant to highly significant differences between genotypes in most vegetative traits, particularly plant height, leaf development, stem diameter, and the length of certain stem segments. Local Red Anggi showed the strongest vegetative performance, particularly in plant height and leaf length, while AMP-UNIPA 5 tended to excel in leaf number and AMP-UNIPA 3 in stem diameter. These results indicate clear vegetative diversity, suggesting that several AMP-UNIPA lines have adaptive potential and are worthy of consideration for further selection.